Religious Moderation Literacy in the PAI Curriculum Canvas: A Genealogical Study of the Concept in K13 and Implementation in the Merdeka Curriculum - Khoirunnisak, Fikri; Ansori, Muhammad (Khalifah : Jurnal Pendidikan Nusantara, 2025)
This genealogical study examines the evolution and implementation of religious moderation literacy within the Islamic Religious Education (PAI) curriculum in Indonesia, focusing on a comparative analysis of the K13 (Kurikulum 2013) and Merdeka (Independent) Curricula. Utilizing a qualitative library research approach with genealogical discourse analysis, the study traces how the concept of religious moderation has been conceptualized, adapted, and operationalized across these two significant educational reforms. Findings indicate a crucial shift from K13's implicit integration of moderation values within broader character education to the Merdeka Curriculum's explicit and systematic articulation of moderasi beragama as a core literacy. The Merdeka Curriculum notably employs more active, student-centered, and experiential pedagogical strategies, contrasting with K13's more content-driven approach. This evolution reflects a growing policy recognition of the need for targeted interventions to foster balanced, tolerant, and inclusive religious understanding. The study contributes to curriculum theory by illustrating how societal needs drive the formalization of values into explicit literacies within educational frameworks, offering valuable insights for curriculum developers and policymakers globally.